PENGARUH KUALITAS PELAYANAN DAN CITRA LEMBAGA TERHADAP WORD OF MOUTH DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA LEMBAGA BELAJAR DIPA LEARNING CENTER DI KOTA MALANG - Marini Wijaya (Jurnal Ekonomi Manajemen dan Bisnis, 2022)
This study analyzes the effect of service quality and institutional image on customer satisfaction, as well as the indirect effect on word of mouth through customer satisfaction in the Dipa Learning Center learning institution Malang. Using a sampling technique with purposive sampling. The instrument for taking questionnaires was 74 respondents, namely parents of students from the Dipa Learning Center learning center who were actively studying for a minimum of 6 months until March 2022. The research data was processed in quantitative description with path analysis techniques using the Smart PLS 3.3.9 application software. The results of this study are supported by primary data using a questionnaire. The results of this study indicate that: (1) Service quality has a significant and significant effect on customer satisfaction; (2) Institutional image has a significant and significant effect on customer satisfaction; (3) Service quality has no significant effect on word of mouth; (4) Institutional image is influential and not significant on word of mouth; (5) Customer satisfaction has a significant and significant effect on word of mouth; (6) Service quality and agency image have a significant and significant effect on customer satisfaction; (7) Service quality and institutional image have an insignificant and insignificant effect on word of mouth through customer satisfaction, and it is not proven that customer satisfaction is an intervening variable.